Geography and strategy - Baum, Joel A. C.; Sorenson, Olav (Emerald, 2003)
As we move into the 21st century, the world seems a smaller place - transportation costs continue to fall, fiber optic networks speed information around the planet, and corporations operate on a global scale. One might reasonably ask whether location really matters anymore. Despite these trends - perhaps because of them - the last few years have witnessed a rapid rise in interest in place and space across the social sciences. While the importance of distance declines, strategic interest in location appears greater than ever. This volume draws together researchers from a variety of disciplines - economics, geography, marketing, organizational behavior, sociology, and urban planning - working at the forefront of this wave to explore some of the important ways in which location matters for firms in the 21st century.